College Students’ Experiences in the Use of Technology in Virtual Classrooms - Oliver C. Logroño; Kharmyn Leah T. Darang; Rholey R. Picaza (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study explores the use of technology and social media during the pandemic among the first-year students of a higher education institution (HEI). This study employed a mixed-methods research design that embodies the principles of descriptive communication research, which entails a systematic examination of the communication process and its essential components. It was discovered that the abilities that the research participants are most familiar with include Word processors, E-mail, Search Engines, and Social Networking, demonstrating how technology may also influence the degree of knowledge in both students and the instructor. The college does a good job of offering services including virtual classrooms, computer labs, learning management systems, ePortfolios, online technologies, software access, and open-source software. However, students still need more time or to be given more opportunities to explore these skills so they can advance their user level. This also reveals their dependency on social media platforms to satisfy a variety of needs.